OTONOMI KHUSUS DAERAH PERBATASAN, ALTERNATIF SOLUSI PENYELESAIAN MASALAH PERBATASAN DI INDONESIA - Permatasari, Ane (Jurnal Media Hukum, 2014)
Border dispute of Indonesia is not a new thing. Since Indonesia got its sovereignty, border had been becoming an unsolved problem until now. A problem that frequently happens is bordered disputes with neighboring countries that have a direct border with Indonesia either land or water borders. In addition, the Indonesian government should pay more attention to problems related to the welfare of people who live in the border. Development and facilities such as education, health, transportation, information and so on should be adequate. The Indonesian government should pay more attention to the needs of people in border areas, therefore they are not segregated from the external world. In accordance with that perspective, this paper would like to identify how the special autonomy of border areas could become the alternative solution to settle disputes in border areas. Generally, poverty and backwardness of people in border areas are the lack of their social and economic accessibility. Border areas have an important function since the complexity of problem that being faced. Border areas should be treated as a front yard, not the back yard of Republic of Indonesia. The treatment for border areas should be differentiated in accordance with the situation and condition of those areas. Therefore, metric decentralization should become the mindset of policy-making related to the relationship between the center and the region, especially related to the border areas and that is not reactive because of the demand of the region. Special autonomy in border areas is an option solution which is worth to be considered, to solve the complex problems in the border areas.